How to finance economic development in the new millennium: German capital exports to Asia and the debate on the effectiveness of official development financing - Peter Nunnenkamp (Kiel Institute of World Economics (IfW), 2000)
Germany's role in financing economic development in Asia on a sustainable basis leaves much to be desired. Direct investors are still underrepresented in the region. Commercial banks have fueled speculative bubbles. Official development financing does not appear to be based on efficiency-related criteria. As concerns development financing in the new millennium, the challenge for relatively advanced emerging market economies is mainly to restructure private capital inflows in order to soften boom and bust cycles. Official development financing needs major reforms in order to promote economic growth, alleviate poverty and support good governance in low-income developing countries.
Keywords: F35; F30; 330; private capital flows; official development assistance; Entwicklungsfinanzierung; Kapitalexport; Direktinvestition; Deutschland; Asien; Entwicklungsländer